Vibrational spectra of barium oxalate hemihydrate - Torres, María Marta (2016)
The infrared and Raman spectra of barium oxalate hemihydrate, BaC2O4 · 0.5H2O, were recorded and discussed on the basis of their structural peculiarities and in comparison with the spectra of the previously investigated calcium and strontium oxalates.